Penerapan Media Labirin Waktu pada Pembelajaran Matematika untuk Meningkatkan Hasil Belajar Siswa Kelas II Sekolah Dasar - Khairunnisa, Firza; Mushlihuddin, Rahmat; Harahap, Anita Santi (ALSYS, 2025)
The low learning outcomes of students in the Mathematics subject in Class II-C at UPT SD Negeri 060913 Medan are caused by the lack of engaging instructional media that align with the characteristics of early-age learners. This study aims to improve student learning outcomes on the topic of time measurement through the implementation of Labirin Waktu media, an educational game-based tool designed to train logic, concentration, and arithmetic skills through time-themed maze challenges. This research is a Classroom Action Research (Penelitian Tindakan Kelas, PTK) conducted in two cycles involving 19 students, with stages including planning, implementation, observation, and reflection in each cycle. Data were collected through observations of teacher and student activities as well as learning outcome tests. The results show an increase in student learning mastery from 57.89% in the pre-cycle to 68.42% in Cycle I, and a significant rise to 89.47% in Cycle II. Additionally, teacher and student activities during the learning process also improved, reflecting active involvement and learning enthusiasm. These findings indicate that Labirin Waktu media is effective in enhancing learning outcomes and student engagement in Mathematics learning. The implication is that this medium can serve as an innovative alternative to create a more meaningful and enjoyable learning process for elementary school students.